Private Practice in Cardiology. Much to offer, much to lose - Dalby, A.J. (SA Heart Journal, 2017)
All the contributions to this edition of SA Heart were invited from authors with connections to private practice. It is therefore noteworthy that two of the six articles include co-authors from the respective academic units in which the invited authors work. Such collaboration illustrates the close links that exist between the private and academic sectors in South Africa. Not only do private practitioners participate in the activities of the teaching units, but, in turn, many of their senior academic staff have ongoing interests also in their own private practices.